Fusion of MR and SPECT Images Using Statistics based Guided Image Filter with Weighted Average Rule - Fathima Zaheera, Dr. SudhagarGovinda Swamy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A fast and effective image fusion method is proposed for creating a highly informative fused image through merging multiple images. The proposed method is based on a two-scale decomposition of an image into a base layer containing large scale variations in intensity, and a detail layer capturing small scale details. A novel Statistics based guided image filtering-based weighted average technique is proposed to make full use of spatial consistency for fusion of the base and detail layers. Experimental results demonstrate that the proposed method can obtain state-of-the-art performance for fusion of multispectral, multi focus, multimodal, and multi exposure images.